Partnership, gender roles and the well-being cost of unemployment - Andreas Knabe; Ronnie Schöb; Joachim Weimann (Center for Economic Studies and ifo Institute (CESifo), 2012)
We use the differences between life satisfaction and emotional well-being of employed and unemployed persons to analyze how a person's employment status affects cognitive well-being. Our results show that unemployment has a negative impact on cognitive, but not on affective well-being, which we interpret as a loss in identity utility. Living in a partnership strengthens the loss in identity utility of men, but weakens that of women. Unemployment of a person's partner reduces the identity loss of unemployed men, but raises it for women. These results suggest that the unemployed's feeling of identity is affected by traditional gender roles, while this does not seem to be the case for the affective part of their subjective well-being.
Keywords: I31; J60; J22; 330; unemployment; happiness; life satisfaction; Day Reconstruction Method; identity; partnership; gender roles; Arbeitslosigkeit; Zufriedenheit; Emotion; Persönlichkeitspsychologie; Geschlecht; Lebensgemeinschaft; Deutschland